Acupuncture for the Treatment of Itch: Peripheral and Central Mechanisms - Tang, Yi; Cheng, Shirui; Wang, Jin; Jin, Yin; Yang, Haodong; Lin, Qihui; Xu, Sanmei; Hui, Lin; Yin, Quanying; Yang, Ying; Wu, Xi (Frontiers in Neuroscience, 2022)
Despite widespread clinical use of acupuncture in the treatment of pruritus caused by psoriasis, urticaria, uremic, and other diseases, insights into the mechanism of action of acupuncture are still emerging. For the above reasons，a beneficial effect of acupuncture on pruritus, was not recommended or reported in recent clinical practice guidelines. Acupuncture is a kind of physical stimulation, which has the characteristics of multi-channel and multi-target effects. The biomechanical stimulation signal of acupuncture needling can be transformed into bioelectric and chemical signals, interfere with kinds of cells and nerve fibers in the skin and muscle, alter signalling pathways and transcriptional activity of cells, mediators and receptors, and result in inhibition of peripheral and central transmission of pruritus. Available mechanistic data give insights into the biological regulation potency of acupuncture for pruritus and provide a basis for more in-depth and comprehensive mechanism research.